Enhancing Vocational Students' Understanding of Macromolecules Properties: A Practical Approach through Laboratory Activities to Support Sustainable Development Goals (SDGs) - Tohe, Humairah Ansar; Munawaroh, Heli Siti Halimatul; Riandi, R.; Nandiyanto, Asep Bayu Dani; Prajayanti, Atiek Octaria; Fiandini, Meli (Journal of Engineering Education Transformations, 2025)
This study aims to develop a chemistry experiment design by utilizing simple tools and materials to teach the concept of macromolecules (carbohydrates, lipids, and proteins) to vocational students. The method used in this research is descriptive-quantitative. The research design was pre-test and post-test one group design. The subjects of this study were 23 students of class X vocational school in Cimahi, West Java, Indonesia. Learning was conducted using conventional methods and supported by practicum activities. Laboratory activities were carried out by conducting experiments using simple tools and materials to understand the physical and chemical properties of carbohydrates, lipids, and proteins. The results of the analysis showed that there was an increase between the pretest and post-test scores of students as shown in the N-Gain value obtained of 0.4 with a moderate category, while hypothesis testing with the Wilcoxon test showed that there is an influence between learning activities assisted by practicum activities on the level of student understanding of macromolecular material. The results of this study show that classroom practice activities are very useful in helping students understand the scientific concepts of macromolecules and can connect theory with practice. In-depth concept understanding of macromolecules also impacts on achieving the Sustainable Development Goals (SDGs).